Tunable Quantum Confinement in Ultrathin, Optically Active Semiconductor Nanowires Via Reverse‐Reaction Growth. (25th February 2015) - Loitsch, Bernhard; Rudolph, Daniel; Morkötter, Stefanie; Döblinger, Markus; Grimaldi, Gianluca; Hanschke, Lukas; Matich, Sonja; Parzinger, Eric; Wurstbauer, Ursula; Abstreiter, Gerhard; Finley, Jonathan J.; Koblmüller, Gregor
<x xml:space="preserve">Abstract</x> A unique growth scheme is demonstrated to realize ultrathin GaAs nanowires on Si with sizes down to the sub‐10 nm regime. While this scheme preserves the bulk‐like crystal properties, correlated optical experiments reveal huge blueshifted photoluminescence (up to ≈100 meV) with decreasing nanowire cross‐section, demonstrating very strong quantum confinement effects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>